Factors influencing the adoption of Facebook as a marketing channel among SMEs in Nigeria as a developing country: a conceptual framework / Idris Na'umma Abdullahi, Mohd Heikal Husin and Ahmad Suhaimi Baharudin - Abdullahi, Idris Na'umma; Husin, Mohd Heikal; Baharudin, Ahmad Suhaimi (Universiti Teknologi MARA, Perlis, 2021)
This paper reviews empirical literature to develop a conceptual framework for the adoption of Facebook as a marketing channel by Small and Medium Enterprises (SMEs) in developing countries like Nigeria. Recent peer-review journal articles were reviewed to develop the conceptual framework for this study. Facebook provides SMEs with a cost-effective strategy for marketing their products and services to both local and international customers. However, SMEs in developing countries like Nigeria are slow in the adoption of Facebook. A literature review has revealed a lack of research on the adoption of Facebook by SMEs from the context of developing countries like Nigeria. Most of the existing studies on Facebook adoption were conducted in developed countries. Findings from such studies cannot be directly applied to SMEs in developing countries because they face different challenges. The paper proposes a conceptual framework based on the Technology-Organization-Environment (TOE) framework that can be empirically tested by a future researcher to determine factors influencing the intention of small and medium enterprises operating in the context of developing countries to adopt Facebook as a marketing channel to enhance their competitive advantage in the modern market. Findings from this study would be beneficial to decision-makers in Nigerian SMEs and Nigerian government agencies with responsibility for strengthening SMEs' activities in the country. It will also encourage and guide SMEs to adopt Facebook as their marketing channel.